HUBUNGAN PENGETAHUAN DAN PERILAKU VULVA HYGIENE SAAT MENSTRUASI DENGAN KEJADIAN PRURITUS VULVAE PADA REMAJA PUTRI KELAS VII DI SMP NEGERI 1 SEPULU BANGKALAN - Annah Hubaedah (EMBRIO, 2019)
Pruritus vulvae is a desease indicated by intching on the external female genitalia. Pruritus vulvae can be caused by bacteria, fungi and viruses. The aim of this research is to investigate the relationship between knowledge and behavior of vulva hygiene during menstruation with pruritus vulvae events on teenage-girls in class VII at SMP Negeri 1 Sepulu Bangkalan. This research employs observasional research method by using cross sectional approach. The population of this research is all female students in class VII at SMP Negeri 1 Sepulu Bangkalan as much as 98 students. The samples are obtained as much as 79 students determined by simple random sampling technique. Questioners are used as the instrument of this research. Besides, it statistically uses lambda. The result showed that there was a relationship between knowledge of vulva hygiene (p=0.028 < α=0.05) and behavior of vulva hygiene (p=0.006 < α=0.05) events during menstruation with pruritus vulvae on teenage-girls in class VII at SMP Negeri 1 Sepulu Bangkalan. Therefore, behavior of vulva hygiene during menstruation are necessary to be increased since having proper, behavior of vulva hygiene will decrease pruritus vulvae events risk.